GE_GERICHTE P/4981/2020 vom 27. Januar 2022 - GE Cour de justice (2022)
IN DUBIO PRO REO;DISPOSITIONS PÉNALES DE LA LCR;VIOLATION DES RÈGLES DE LA CIRCULATION;CONTRAVENTION | LCR.90; LCR.26.al1; OCR.14; CPP.429.al1.leta